2018
DOI: 10.1111/fcp.12351
|View full text |Cite|
|
Sign up to set email alerts
|

Agmatine co‐treatment attenuates allodynia and structural abnormalities in cisplatin‐induced neuropathy in rats

Abstract: Cisplatin is a widely used antineoplastic agent in the treatment of various cancers. Peripheral neuropathy is a well-known side effect of cisplatin and has potential to result in limiting and/or reducing the dose, decreasing the quality of life. Thus, effective treatments are needed. Agmatine is an endogenous neuromodulator that has been shown to exert antiallodynic effects in various animal studies. The first aim of this study was to investigate the in vitro effects of agmatine on cisplatin-induced neurotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…41 Furthermore, the difference in the dosing schedule may explain the disagreement in the behavioural results, because acute administration with cisplatin in our study and in the previously mentioned study by Ali et al resulted in hypoalgesia, 33 whereas the other aforementioned studies reported ensuing hyperalgesia with administration of repeated doses of cisplatin. 39,40 Our results of the locomotor activity and neuromuscular coordination tests are in agreement with previous works showing cisplatin-induced reduction in locomotor activity 42,43 and grip strength. 44,45 On the other hand, coadministration with PIC (10 mg/kg) attenuated the aforesaid cisplatin-induced behavioural changes in the hotplate, tail flick and writhing tests, in addition to the motor results in the locomotor activity and the neuromuscular coordination tests.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…41 Furthermore, the difference in the dosing schedule may explain the disagreement in the behavioural results, because acute administration with cisplatin in our study and in the previously mentioned study by Ali et al resulted in hypoalgesia, 33 whereas the other aforementioned studies reported ensuing hyperalgesia with administration of repeated doses of cisplatin. 39,40 Our results of the locomotor activity and neuromuscular coordination tests are in agreement with previous works showing cisplatin-induced reduction in locomotor activity 42,43 and grip strength. 44,45 On the other hand, coadministration with PIC (10 mg/kg) attenuated the aforesaid cisplatin-induced behavioural changes in the hotplate, tail flick and writhing tests, in addition to the motor results in the locomotor activity and the neuromuscular coordination tests.…”
Section: Discussionsupporting
confidence: 92%
“…39 Likewise, a previous study showed no difference in the paw withdrawal latency between cisplatin and the control in the hotplate test; such variation from our results may be attributed to the lower cisplatin dose they used (3 mg/kg), administered once a week for 5 weeks. 40 Indeed, an earlier study resolved such inconsistency and reported that higher doses of cisplatin induced hypoalgesia, whereas lower doses produced hyperalgesia. 41 Furthermore, the difference in the dosing schedule may explain the disagreement in the behavioural results, because acute administration with cisplatin in our study and in the previously mentioned study by Ali et al resulted in hypoalgesia, 33 whereas the other aforementioned studies reported ensuing hyperalgesia with administration of repeated doses of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that L-NAME did not significantly potentiate the antiallodynic and neuroprotective effects of agmatine. 139 It was demonstrated that NOS inhibitors and NMDA receptor antagonists could increase the release of 5-HT by activating tryptophan hydroxylase. 140 It can be thought that the increase in serotonin could contribute the antinociceptive activity of agmatine.…”
Section: Antinociceptive Effects Of Agmatine In Animal Models Of Npmentioning
confidence: 99%
“…The primary cultures of DRG were prepared as previously described [24]. Rats were purchased from Medical and Surgical Research Center of Eskisehir Osmangazi University.…”
Section: Drg Isolation and Cell Culturementioning
confidence: 99%